Faktor – Faktor yang Berhubungan dengan Rendahnya Kunjungan Antenatal Care K1 Murni di Puskesmas Lembo Kabupaten Konawe Utara Periode Mei-Juli Tahun 2015 - Pakkan, Rosmiati (Jurnal Gizi Ilmiah, 2017)
Antenatal care (pregnancy check-ups) is very important for pregnant women to know because it can help reduce maternal and infant mortality. Another advantage is to keep them healthy during pregnancy, delivery and postpartum and to make sure that babies are born healthy, while Pure K1 is the number of first contacts. pregnant women with health workers at gestational age 12 weeks. This study aims to determine the relationship between knowledge, attitudes, and family support with low pure K I antenatal care visits at Puskesmas Lembo Kab. North Konawe. This type of research is an analytic survey with a cross sectional study design, where the population is pregnant women in the working area of ​​the Lembo Health Center, Kab. North Konawe in 2015 as many as 51 people. Sampling using simple random sampling technique, obtained 45 respondents randomly. Data collection was carried out using a questionnaire. The data that has been collected is then processed and analyzed using statistics (SPSS) version 17.0. Data analysis includes univariate analysis by looking for the frequency distribution, bivariate analysis by using chis square test. The results of statistical test analysis showed that there was a relationship between knowledge and low antenatal care visits. x2Hit = 18,687 > x2Tab = 3.841 with p value = 0.000, there was a relationship between attitude and low antenatal care visits. Pure KI value x2Hit = 25.527 > x2Tab = 3.841 with p value = 0.000 there is a relationship between family support and low KI antenatal care visits. The value of x2 Hit = 16,703 > x2Tab = 3.841 with p value = 0.000. So there is a need for pure K1 antenatal care socialization for pregnant women